Survey on first-line therapeutic management of relapsing–remitting multiple sclerosis in clinical practice in Spain - M. Llaneza; G. Fontes; L. Benedito-Palos; E. Moral (Neurology Perspectives)
Introduction: Current therapies for relapsing–remitting multiple sclerosis (RRMS) help reduce morbidity and delay disease progression. However, the available information on factors influencing decision-making regarding first-line treatment remain poorly understood. Methods: Based on a review of the literature and the experience of a scientific committee made up by 2 neurologists, an ad hoc survey was developed and distributed to Spanish neurologists. It included 22 questions related to the first-line therapeutic management of RRMS. Results: Sixty neurologists (mean age: 45.6 years, 60% women, mean of 16.0 years of experience, mean of 93.8 patients with RRMS attended/month) participated in the study. Neurologists considered that the 3 most important treatment characteristics (1–8 points, with higher scores denoting greater relevance) in treatment decision-making were efficacy in disease control (7.8±0.5), safety/tolerability (6.7±0.9), and improvements in patient quality of life (5.0±1.5); regarding patient characteristics, the 3 most important (1–7 points) were disease activity (6.9±0.5), intention to become pregnant (5.0±1.0), and level of disability (4.3±1.8). Dimethyl fumarate (32.6%) was the most frequently prescribed treatment, followed by teriflunomide (24.8%) and glatiramer acetate (17.6%). According to over 87% of the specialists, the latter drug was considered the most appropriate treatment for patients with liver disorders, who intended to become pregnant, and who presented low disease activity. Conclusions: Our study provides evidence on the first-line therapeutic management of non-aggressive forms of RRMS and the factors influencing decision-making in routine clinical practice. Resumen: Introducción: Las terapias actuales para la esclerosis múltiple recurrente-remitente (EMRR) ayudan a reducir la morbilidad y retrasar la progresión de la enfermedad. Sin embargo, la información disponible sobre los factores que influyen en la elección de la terapia de primera línea (1 L) es limitada. Método: Con base a una revisión de la literatura y la experiencia de un Comité científico formado por dos neurólogos se elaboró un cuestionario ad-hoc dirigido a neurólogos españoles que incluía 22 preguntas relacionadas con el abordaje terapéutico en 1 L de la EMRR. Resultados: Sesenta neurólogos (edad media: 45,6 años, 60% mujeres, experiencia previa: 16,0 años, media de pacientes con EMRR atendidos/mes: 93,8) participaron en la encuesta. Las tres características del tratamiento consideradas más importantes (1 = menos-8 = más importante) para la toma de decisiones fueron la eficacia en el control clínico de la enfermedad (7,8 ± 0,5), la seguridad/tolerabilidad (6,7 ± 0,9) y la mejora de la calidad de vida (5,0 ± 1,5); y del paciente (1 = menos-7 = más importante), la actividad de la enfermedad (6,9 ± 0,5), el deseo gestacional (5,0 ± 1,0) y el grado de discapacidad (4,3 ± 1,8). El dimetil fumarato (32,6%) es el tratamiento más frecuentemente prescrito, seguido de la teriflunomida (24,8%) y el acetato de glatiramero (17,6%). Este último es el considerado más adecuado para pacientes con trastorno hepático, deseo gestacional y una baja actividad de la enfermedad, según más del 87% de los especialistas. Conclusiones: Nuestro estudio aporta evidencia sobre el manejo terapéutico en 1 L de las formas no agresivas de la EMRR y de los factores que influyen en la toma de decisiones en la práctica clínica habitual.